B2B digital marketing strategy : how to use new frameworks and models to achieve growth - Hall, Simon, 1971- (London ; : Kogan Page, 2020)
"B2B Digital Marketing Strategy is a decisive guide to the most recent developments in the field. It gives readers an overview of the latest frameworks and models, and shows how these can be used to overcome the everyday challenges associated with account targeting, data utilization, and digital campaign management. Intensely practical, B2B Digital Marketing Strategy helps readers get to grips with some of the more advanced and complex elements of B2B marketing. It expertly explains how to incorporate the latest digital methodologies into critical processes such as lead generation, customer retention and customer experience personalization. Packed with global case studies and examples, this book is an invaluable resource for any professional operating in the B2B space"--
Includes bibliographical references and index.
Keywords: B2B ; digital marketing; Data transmission systems; Internet marketing; Social media